In search of a strategy for making growth more pro-poor in the Philippines - Nobuhiko Fuwa; Arsenio M. Balisacan; Fabrizio Bresciani (University of the Philippines, School of Economics (UPSE), 2011)
The main driver of poverty reduction has shifted from agricultural to non-agricultural income growth in rural Philippines in the past two decades. Agricultural growth is still relatively more important (vis-à-vis non-agricultural growth), however, in reducing rural poverty in relatively more isolated provinces. Our results suggest that agricultural investments should focus on areas with underdeveloped infrastructure but with comparative advantage in agriculture. At the same time, non-agricultural income growth can be made more pro-poor by investing in mobility infrastructure and health, facilitating international labor migration, and lowering income inequality.
Keywords: I32; O13; O15; O40; 330; poverty; growth and inequality; pro-poor growth; role of agriculture; the Philippines; Asia; Armut; Wirtschaftswachstum; Soziale Ungleichheit; Landwirtschaftliche Entwicklung; Philippinen